DEVELOPMENT OF PROFESSIONAL COMPETENCES OF STUDENTS - Hamrayeva Aziza Farhadovna (American Journals, 2023)
The formal structure of the system of professional pedagogical training in higher education consists of a set of teachers, teaching aids, students and teaching technologies. This article discusses the importance of developing the professional competence of teachers.
Keywords: professional pedagogical training, creativity, inquisitiveness, dedication, professional competence, pedagogue, teaching technologies, professional pedagogical activity.